Safety and efficacy of alternating treatment with EP2006, a filgrastim biosimilar, and reference filgrastim: a phase III, randomised, double-blind clinical study in the prevention of severe neutropenia in patients with breast cancer receiving myelosuppressive chemotherapy. (28th October 2017) - Blackwell, K; Gascon, P; Krendyukov, A; Gattu, S; Li, Y; Harbeck, N
Abstract: Background: In 2015, the biosimilar filgrastim EP2006 became the first biosimilar approved by the US Food and Drug Administration for commercial use in the United States, marketed as Zarxio ® (Sandoz). This phase III randomised, double-blind registration study in patients with breast cancer receiving (neo)adjuvant myelosuppressive chemotherapy (TAC; docetaxel + doxorubicin + cyclophosphamide) compares reference filgrastim, Neupogen ® (Amgen), with two groups receiving alternating treatment with reference and biosimilar every other cycle. Patients and methods: A total of 218 patients receiving 5 µg/kg/day filgrastim over six chemotherapy cycles were randomised 1: 1: 1: 1 into four arms. Two arms received only one product, biosimilar or reference (unswitched), and two arms (switched) received alternating treatments every other cycle (biosimilar then reference or vice versa over six cycles). Since the switch occurred from cycle 2 onwards, this analysis compared pooled switched groups to the unswitched reference group for efficacy during cycles 2–6. Safety was also assessed. Non-inferiority in febrile neutropenia (FN) rates between groups for cycles 2–6 was shown if 95% were within a pre-defined margin of − 15%. Results: A total of 109 patients switched treatment, and 52 patients received reference in all cycles. Baseline characteristics were similar between groups. The incidence of FN was 0% (reference) versus 3.4% ( n = 3, switched) across cycles 2–6, with a difference of − 3.4% (95% confidence interval: −9.65% to 4.96%), showing non-inferiority. Infections occurred in 9.3% (switched) versus 9.9% (reference). Hospitalisation due to FN was low (one patient in cycle 6; switched). Adverse events related to filgrastim were reported in 42.1% (switched) versus 39.2% (reference) (all cycles). Musculoskeletal/connective tissue disorders related to filgrastim occurred in 35.5% (switched) versus 39.2% (reference) (all cycles), including bone pain (30.8% versus 33.3%). No neutralising antibodies were detected. Conclusions: There were no clinically meaningful results regarding efficacy, safety or immunogenicity when switching from reference to biosimilar filgrastim/EP2006, or vice versa.